PENGARUH KINERJA KEPALA DESA TERHADAP PENINGKATAN PRESTASI KERJA PERANGKAT DESA (STUDI PADA DESA SUMBERGEDE, KECAMATAN SEKAMPUNG, LAMPUNG TIMUR)) - Department, administratio; Widodo, Wahyu (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2017)
ABSTRACT. The development of rural areas is inseparable from the participation of all rural communities, so that the performance of a village head as the head of the village administrationshould be able to carry out the main duties of leading and coordinating the village administration inimplementing some village household affairs, fostering and building the community, and fosteringthe village economy . In reality, however, it shows that the village head's performance appraisal bythe community in providing sluggish, slow, and convoluted service and formality. By usingquantitative approach, this study aims to determine the performance of Village Head to improveperformance of village apparatus. Because the population of 15 people, the authors will take theentire sample of research to be a population of 15 people village devices. The result of this researchconclude that there is influence of performance of Village Head to improvement of work performanceof village apparatus with r count 0,69> r table 0,641. Keywords: performance, job performance, village apparatus